Development of IoT-Based Heart Rate and Oxygen Saturation Alert System for COVID-19 Wards - Ravindran, Darrshiny; Jumadi, Nur Anida (Evolution in Electrical and Electronic Engineering, 2022)
The increasing number of Coronavirus Disease 2019 (COVID-19) patients gives it a tough time for the hospital staff to manage and monitor the patient’s oxygen levels and heart rate. Therefore, this research was done to create an alert system that enables the hospital staff to monitor and provide immediate care for COVID-19 patients who experience a drop in oxygen saturation (SpO2) and heartbeat levels. The objectives of this research were to develop the heart rate and oxygen saturation system, to develop the alert notification system using a buzzer, ThingSpeak, and SMS, and to evaluate the performance of the developed system. For the hardware development, two MAX30102 sensors, a NodeMCU ESP8266, an Arduino UNO, two OLED Displays (0.96in 128x64 SSD1306 Blue), and two buzzers were used. The integration with ThingSpeak allowed the data to be displayed and monitored. The IFTTT played an important role in allowing notifications through SMS to the users. The buzzer successfully beeped, and the alert notification was sent to the authorized personnel in the form of SMS when the SpO2 dropped below 94%, BPM was less than 60 and when exceed 120. Obtaining a   high degree of accuracy is the goal of the research's future work since it is important to verify the device's accuracy and to conduct the measurement in an appropriate setting.